2022
DOI: 10.1039/d2ra04897c
|View full text |Cite
|
Sign up to set email alerts
|

Nickel sulfide and phosphide electrocatalysts for hydrogen evolution reaction: challenges and future perspectives

Abstract: A comprehensive overview of nickel sulfide and phosphide electrocatalysts in the HER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…In recent years, hydrogen energy, which has the advantages of zero pollution, zero carbon emission, low molecular weight, highenergy density, abundant reserve and supply, has been known as a viable alternative energy resources. 1,2 In general, electrochemical water splitting is an ideal approach for producing green hydrogen gas without the emission of any polluting gases. 3 Hydrogen production from water electrolysis usually involves two reactions: the cathodic hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrogen energy, which has the advantages of zero pollution, zero carbon emission, low molecular weight, highenergy density, abundant reserve and supply, has been known as a viable alternative energy resources. 1,2 In general, electrochemical water splitting is an ideal approach for producing green hydrogen gas without the emission of any polluting gases. 3 Hydrogen production from water electrolysis usually involves two reactions: the cathodic hydrogen evolution reaction (HER) and the anodic oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen evolution reaction (HER) is, however, still limited by the large overpotential that is found in splitting H 2 O, which makes the reaction performance hover at a significantly lower level. It has been shown that certain noble metals with the low overpotential, such as platinum-based materials, are expected to serve as excellent catalysts for hydrogen production in practical application, though the scarcity of these materials and the high price make them difficult to use in practice [ 11 , 12 , 13 , 14 ]. To solve HER problems, we need efficient non-precious metal electrocatalysts [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] In particular, nickel-based suldes and phosphides are identied as effective electrocatalytic materials for the HER in acidic media due to their good electrical conductivity and valuable intrinsic activity. [16][17][18][19] However, the HER performances are still not giving satisfactory results due to the lack of electrical contact between the electrolyte and supporting electrocatalyst, adjustable active sites, and limited charge transport process. [20][21][22][23] To date, the transition metal-based heterostructure phase (metal sulde-selenide, sulde-oxide, selenide-phosphide, and sulde-phosphide) achieved signicant importance for the design of high performance HER electrocatalysts due to the interplay between the two different phases, whereas the intrinsic catalytic activity of the individual phase is different.…”
Section: Introductionmentioning
confidence: 99%